LAPAROSCOPIC URETEROCALICOSTOMY IN EXTENT RECURRENT STRICTURE OF RIGTH URETEROPELVIC JUNCTION - B. K. Komiakov; B. G. Guliev; T. Kh. Al-Attar (Вестник урологии)
The article presents the result of laparoscopic ureterocalicostomy. We observed the patient 39 y. who was admitted with complaints of aching pain in right lumbar part. 10 years ago he was underwent open pyeloplasty. In 2017 again there were pain in right kidney. At examination on CT with intravenous urography is revealed extended stricture of ureteropelvic junction, intrarenal pelvis, dilated pelvi-caliceal system and thin parenchyma under lower calyx. In flank position using transperitoneal approach we mobilized upper third of right ureter, transected distally of stricture and performed anastomosis with lower calyx.  Operative time 110 min, bloodloss – 50 ml. No intra- and postoperative complications. Drain removed in 2 days, nephrostomic drain – in 7 days. Stent removed after 6 weeks. In a follow-up survey the patient haven’t any complaints, and a moderate expansion of the renal pelvicaliceal system on ultrasound.